2014
DOI: 10.1007/s12223-014-0352-0
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of microbial communities in two shallow peat bog lakes

Abstract: Peat bog lakes represent important ecosystems in temperate and boreal zones. We investigated the seasonal dynamics of the microbial community in two small peat bog lakes, Kuźnik Olsowy and Kuźnik Bagienny, located in western Poland. Fluorescence in situ hybridization analyses revealed that the bacterial community was dominated by Proteobacteria and Actinobacteria, in addition to a substantial number of archaea. An infrared epifluorescence analysis demonstrated that aerobic anoxygenic phototrophs (AAPs) constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 43 publications
7
21
0
Order By: Relevance
“…However, its effect under natural conditions remains in‐conclusive. A positive correlation between AAP numbers and day length has been found during the seasonal studies in Mediterranean coastal waters and lagoons (Lamy et al, 2011, Ferrera et al, 2014), but such effect was not observed in freshwater lakes (Mašín et al, , Čuperová et al, 2012, Lew et al, ). Moreover, no clear effect of light was found in direct, short‐term experiments (Schwalbach et al, , Stegman et al, , Garcia‐Chaves et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its effect under natural conditions remains in‐conclusive. A positive correlation between AAP numbers and day length has been found during the seasonal studies in Mediterranean coastal waters and lagoons (Lamy et al, 2011, Ferrera et al, 2014), but such effect was not observed in freshwater lakes (Mašín et al, , Čuperová et al, 2012, Lew et al, ). Moreover, no clear effect of light was found in direct, short‐term experiments (Schwalbach et al, , Stegman et al, , Garcia‐Chaves et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…AAP bacteria are abundant in various marine environments (Kolber et al, , Cottrell et al, , Sieracki et al, , Jiao et al, , Yutin et al, , Boeuf et al, ) and also in many freshwater lakes and rivers (Mašín et al, , Mašín et al, , Ruiz‐González et al, , Čuperová et al, , Caliz and Casamayor, , Fauteux et al, , Lew et al, ). Freshwater AAP bacteria seem to represent a diverse assemblage of species belonging exclusively to different subgroups of Alpha‐ and Betaproteobacteria (Waidner and Kirchman, , Shi et al, , Salka et al, , Čuperová et al, , Caliz and Casamayor, ).…”
Section: Introductionmentioning
confidence: 99%
“…AAPs also represent a common component of freshwater microbial communities. Large numbers of AAPs were reported for temperate lakes (7)(8)(9), peat bogs (10), and rivers (11), frequently correlating with the trophic state and temperature (12). Cultivation-independent approaches showed that AAPs represent a phylogenetically heterogeneous group that includes different clades of Alphaproteobacteria, Gammaproteobacteria, and Betaproteobacteria (13,14).…”
Section: Importancementioning
confidence: 99%
“…Particle associating ability, depth (which defi nes a wide range of physical and chemical parameters), pH, dispersion opportunities, resource availability, disturbance and physical chemical heterogeneity of the environment also play decisive role in forming the community structures [25]. Lew et al [27] found large seasonal changes of bacterial community composition and Proteobacteria and Actinobacteria dominance during the microbial investigation of two peat bog lakes. The study also pointed out the infl uence of organic matter originated from peat moss on forming the microbial communities.…”
Section: Acta Microbiologica Et Immunologica Hungarica 63 2016mentioning
confidence: 99%
“…A previous study on the microbiota of 15 freshwater lakes using reverse line blot hybridization based on 16S rRNA gene showed similar results to present investigation regarding the identifi ed phyla and classes of Proteobacteria. However, representatives of phylum Verrucomicrobia, those were also found then and are often revealed form freshwater [27], was not identifi ed from the water of Lake Hévíz. Furthermore, the study specifi ed three parameters such as pH, hydrological retention time and temperature as the strongest environmental factors infl uencing the microbial communities.…”
Section: Acta Microbiologica Et Immunologica Hungarica 63 2016mentioning
confidence: 99%